Chapter Securing the Home Energy Management Platform - Aagaard Mikkelsen, Soren (InTechOpen, 2016)
Recently, many efforts have been done to chemically functionalize sensors surface to achieve selectivity towards diagnostics targets, such as DNA, RNA fragments and protein tumoural biomarkers, through the surface immobilization of the related specific receptor. Especially, some kind of sensors such as microcantilevers (gravimetric sensors) and one-dimensional photonics crystals (optical sensors) able to couple Bloch surface waves are very sensitive. Thus, any kind of surface modifications devoted to functionalize them has to be finely controlled in terms of mass and optical characteristics, such as refractive index, to minimize the perturbation, on the transduced signal, that can affect the response sensitivity towards the detected target species.